Sports and governance : pole-vaulting into the 21st century - Juico, Philip Ella (Manila : De La Salle University Press, 2000)
This book is about sports, history and empowerment. To my mind, it is the first book written by a Filipino that straddles sports policy, management and administration, and history. Its strength lies in the broad perspectives from which Philip Ella Juico wrote it.
Fitness, stamina and power -- Toughness -- Linking with the man -- Lifelong enthusiasm -- Sports and national development -- Linking with Ming -- The Sportsman as boss -- Golf, physical fitness and governance -- Development and dissonance -- Mainstreaming sports development -- Where do we go from here?
Includes index.
Keywords: PHILIPPINES -- SPORTS POLICY; SPORTS POLICY